DETERMINANTS OF INDONESIA'S CINNAMON EXPORT PERFORMANCE: A SEM–PLS ANALYSIS - Elpawati; Dita Milih Anggraeni (AGRIBUSINESS JOURNAL, 2025)
Indonesia is the world's largest cinnamon exporter by volume, but still lags behind Sri Lanka in terms of export value. This study aims to analyze the factors influencing the competitiveness of Indonesian cinnamon exports in the 2014-2024 period.. Using UN Comtrade data and the SEM-PLS approach, this study identified four main constructs: Product Innovation, Product Quality, Cost Efficiency, and Export Competitiveness. The results show that Product Innovation has a significant effect on Product Quality (β=0.742, p<0.001), which in turn affects Export Competitiveness (β=0.658, p<0.001). Cost Efficiency is also proven to have a significant effect on Export Competitiveness (β=0.284, p<0.05). The model is able to explain 67.3% of the variance in Indonesian cinnamon Export Competitiveness.